Methods of Forming Humanity Characters in Children in Cooperation with Preschool Educational Institution and Family (Eurasian Journal of Learning and Academic Teaching, 2023)
This article describes ways to positively influence the formation of various national traditions and customs based on responsibility and humanity in children on the basis of family cooperation in the upbringing of the young generation, through which virtues, qualities, traditions, The specific aspects of ways of instilling values are highlighted